Lo fantástico, lo agnóstico y lo ancestral en la literatura de Jorge Luis Borges - Marín Calderón, Norman (2013)
This article suggests that texts written by Borges can be read through the coordinates offered by the theory of fantastic literature; that is, metatextuality, the dream work, time, and the double. On the same token, Borges employs different themes about ancient civilizations and agnostic philosophies with the intention to corroborate the fundamental idea of his work that manifests that the fantastic is an alternate sort of the so called reality.